PETROGENESIS OF GOLD-BEARING DIORITOIDS OF THE KETKAP-YUNA MAGMATIC PROVINCE, ALDAN SHIELD - Khanchuk A.I.; Polin V.F.; Tsurikova L.S.; Dril S.I.; Sandimirova G.P. (My University, 2006)
Significant volumes of subalkaline magmatic rocks in the continental crust of the Aldan Shield raises problems concerning their sources in the context of geodynamics, continental growth, and crustal recycling. Our research was aimed at petrogeochemical and geodynamic typification of the Jurassic–Early Cretaceous Uchur (Oblachnyi) Complex of subalkaline trachyandesite–diorite–granodiorites in order to decipher its tectonic setting and petrogenesis. The Uchur Complex is developed in the Ketkap–Yuna magmatic province, which represents a zone of Late Mesozoic tectonomagmatic activation of the shield. This issue is also of practical interest, because subalkaline quartz diorites of the third phase of this complex host economic gold mineralization.
Keywords: Aldan Shield; Ketkap–Yuna Magmatic Province; gold-bearing dioritoids; Мезозой::Меловая; Мезозой::Юрская